Enceladus: An Active Cryovolcanic Satellite - Spencer, John R.; Barr, Amy C.; Esposito, Larry W.; Helfenstein, Paul; Ingersoll, Andrew P.; Jaumann, Ralf; McKay, Christopher P.; Nimmo, Francis; Waite, J. Hunter (Springer, 2009)
Enceladus is one of the most remarkable satellites in the solar system, as revealed by Cassini's detection of active plumes erupting from warm fractures near its south pole. This discovery makes Enceladus the only icy satellite known to exhibit ongoing internally driven geological activity. The activity is presumably powered by tidal heating maintained by Enceladus' 2:1 mean-motion resonance with Dione, but many questions remain. For instance, it appears difficult or impossible to maintain the currently observed radiated power (probably at least 6 GW) in steady state. It is also not clear how Enceladus first entered its current self-maintaining warm and dissipative state- initial heating from non-tidal sources is probably required. There are also many unanswered questions about Enceladus' interior. The silicate fraction inferred from its density of 1:68gcm−2 is probably differentiated into a core, though we have not direct evidence for differentiation. Above the core there is probably a global or regional liquid water layer, inferred from several models of tidal heating, and an ice shell thick enough to support the ~1 km amplitude topography seen on Enceladus. It is possible that dissipation is largely localized beneath the south polar region. Enceladus' surface geology, ranging from moderately cratered terrain to the virtually crater-free active south polar region, is highly diverse, tectonically complex, and remarkably symmetrical about the rotation axis and the direction to Saturn. South polar activity is concentrated along the four “tiger stripe” fractures, which radiate heat at temperatures up to at least 167K and are the source of multiple plumes ejecting ~200kgs−2 of H2O vapor along with significant N2 (or C2H4), CO2, CH4, NH3, and higher-mass hydrocarbons. The escaping gas maintains Saturn's neutral gas torus, and the plumes also eject a large number of micron-sized H2O ice grains that populate Saturn's E-ring. The mechanism that powers the plumes is not well understood, and whether liquid water is ...